PERANAN DINAS PERTANIAN DALAM PEMBERDAYAAN KELOMPOK TANI DI KECAMATAN MANUJU KABUPATEN GOWA - Sholihin Ali; Muhammad Idris; Anwar Parawangi (Department of Government Studies Universitas Muhammadiyah Makassar, 2014)
The purpose of this study is to determine the role of the Department of Agriculture in the empowerment of farmers' groups in the District Manuju Gowa and identify the factors supporting and inhibiting factors in the empowerment of farmer groups. This type of research used was descriptive research and data analysis is the analysis of qualitative data. While data collection techniques used by researchers is the observation, interview and documentation. The results of this study indicate that the role of the Department of Agriculture in the empowerment of farmers' groups in the District Manuju Gowa which include the delivery of training and counseling, help seed and fertilizer, and assistance agricultural technologies. The factors supporting in the empowerment of farmer groups in the District Manuju namely the support of the Central Government in the form of budget allocations in the state budget, help the Provincial Government, District Government. Then factor inhibiting in the empowerment of farmers' groups in the District Manuju is the application of what is obtained by the groups of training and counseling is still lacking because most still use traditional patterns of farming. Besides the lack of seed stock and fertilizer from the manufacturer is still less. Tujuan penelitian ini untuk mengetahui peranan Dinas Pertanian dalam pemberdayaan kelompok tani di Kecamatan Manuju Kabupaten Gowa dan mengidentifikasi faktor-faktor pendukung dan faktor faktor penghambat dalam pemberdayaan kelompok tani. Jenis penelitian yang di gunakan adalah penelitian deskriptif dan analisis data yaitu analisis data kualitatif. Sedangkan teknik pengumpulan data yang di gunakan peneliti adalah observasi, wawancara dan dokumentasi. Hasil penelitian ini menunjukkan bahwa peranan Dinas Pertanian dalam pemberdayaan kelompok tani di Kecamatan Manuju Kabupaten Gowa yang meliputi pemberian pelatihan dan penyuluhan, Bantuan bibit dan pupuk, dan bantuan teknologi pertanian. Adapun faktor pendukung dalam pemberdayaan kelompok tani di Kecamatan Manuju yaitu adanya bantuan dari Pemerintah Pusat berupa alokasi anggaran dalam APBN, bantuan Pemerintah Provinsi, Pemerintah Kabupaten. Kemudian faktor yang menghambat dalam pemberdayaan kelompok tani di Kecamatan Manuju adalah pengaplikasian dari apa yang didapatkan oleh kelompok tani dari pelatihan dan penyuluhan itu masih kurang karena kebanyakan masih menggunakan pola-pola tradisional dalam bertani. Selain itu kurangnya stok bibit maupun pupuk dari produsen.